Integrasi NIK–NPWP Dan Dampaknya Terhadap Kepatuhan Wajib Pajak Di Indonesia: Sebuah Literature Review - Khoirunnisa Khoirunnisa; Ida Farida Adi Prawira; Rika Nurrizkiana (Universitas Katolik Soegijapranata, Semarang, 2026)
This study reviews the integration of Indonesia’s national identification system (NIK) with the tax identification number (NPWP) and examines its potential implications for taxpayer compliance within the broader agenda of tax administration reform. Unlike previous studies that primarily focus on normative discussions or isolated administrative impacts, this literature review synthesizes insights from tax compliance theory, digital tax administration, identity integration, and behavioral fiscal studies. Using a narrative review approach, relevant academic publications, policy documents, and international reports were analyzed to map conceptual linkages between digital identity integration and tax compliance outcomes. The findings indicate that administrative simplification, digitalization, and communication strategies significantly affect compliance levels, although technical and behavioral barriers persist. Based on these results, the study recommends strengthening integrated digital services, improving taxpayer outreach, and enhancing institutional coordination in order to optimize policy outcomes and increase voluntary compliance.